Genome-wide identification of the TIFY gene family in Helianthus annuus and expression analysis in response to drought and salt stresses - Kangping Zhang; Yaxi Zhou; Yuanyuan Jiang; Yaqi Zhou; Jinhui Song; Jingjing Zhang; Jianzhong Guo; Lin Li; Xianping Zhang (Scientific Reports)
Abstract Given the increasing recognition of frequent drought problems associated with global warming, sunflower (Helianthus annuus L.) has been widely studied as a model plant tolerant to drought and salt stresses. However, there is a lack of information on the systematic identification of the sunflower HaTIFY gene family. In the present study, 21 HaTIFY genes in sunflower were identified and the members of HaTIFY family were divided into four subfamilies, i.e., TIFY, JAZ, ZML and PPD. Gene duplication is a major driver for the expansion of the gene family. Here, three segmental and two tandem duplicated gene pairs were identified via duplication and synteny analysis. Furthermore, five paralogous TIFY gene pairs might have undergone purifying selective pressure during evolution based on Ka/Ks ratio. HaJAZ2/4/5/9/12 from JAZ V subfamily were highly expressed in the majority of tissues. In the analysis of promoter elements of HaTIFYs, more than half of 21 HaTIFY genes contained the drought induction elements. Notably, HaPPD1 and HaPPD4 were significantly upregulated at the early stages of both drought and salt treatments, highlighting their potential roles in enhancing sunflower resistance to abiotic stresses. In conclusion, the HaTIFY gene family plays a crucial role in the positive regulation of sunflower’s response to abiotic stresses, offering key candidate genes for enhancing resistance in sunflower breeding programs.